Overview of the Effect of Storage Duration of Sweet Orange Juice (Citrus sinensis L.) on Bacterial Count Using the MPN (Most Probable Number) Method - Hariyanis Hariyanis; Sutriswanto Sutriswanto; Supriyanto Supriyanto (MEDICA (International Medical Scientific Journal), 2024)
Sweet oranges (Citrus sinensis L.) are rich in nutrients that support overall health, particularly brain function. They contain essential components such as vitamin C, folic acid, phytochemical fibers, and various minerals including calcium, potassium, and magnesium. These nutrients may contribute to the prevention of conditions such as cancer, kidney stones, digestive disorders, high cholesterol, and hypertension. This study aimed to determine the bacterial count in sweet orange juice using the Indonesian National Standard (SNI) No. 3719-20 method at room temperature. The research was conducted as a descriptive observational study. Sweet oranges were purchased from the Amifruts Shop in Pontianak. The juice was extracted and diluted with water at a 1:1 ratio, then divided into five samples and stored at room temperature for 2, 3, 4, 5, and 6 hours, respectively. Samples were cultured on LB media and incubated at 37°C for 24 hours to observe bacterial growth, indicated by changes in the medium. Based on the Most Probable Number (MPN) method, two samples tested positive for coliform bacteria, with an estimated bacterial count of approximately 25. It can be concluded that there was some Coliform bacterial contamination at specific times.